Bambi - Disney; Walt (England Parragon Books, 2016)
Bambi, the young prince of the forest, as he learns valuable lessons about friendship, love, and the miracle of life. With beloved characters like Thumper the bunny, this deluxe storybook retelling of the classic animated film is a treasure to behold. Ages 7+